2015
DOI: 10.1590/0031-1049.2015.55.06
|View full text |Cite
|
Sign up to set email alerts
|

A new genus and two new species of Xustrostomatidae Hunt, 2002 (Nematoda: Rhigonematomorpha) from the West Indies

Abstract: A new genus and two new species of xustrostomatids (Nematoda

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…were closely related with the family Xustromatidae ( Trachyglossoides sp. ), since species of Rhigonema , for example R. thysanophora , have a very different morphology of cephalic end and esophagus when compared with members of the Xustromatidae [ 66 , 67 ]. The evolutionary relationships of the three families Rhigonematidae, Ichthyocephalidae and Xustromatidae in the Rhigonematoidea remain unsolved.…”
Section: Discussionmentioning
confidence: 99%
“…were closely related with the family Xustromatidae ( Trachyglossoides sp. ), since species of Rhigonema , for example R. thysanophora , have a very different morphology of cephalic end and esophagus when compared with members of the Xustromatidae [ 66 , 67 ]. The evolutionary relationships of the three families Rhigonematidae, Ichthyocephalidae and Xustromatidae in the Rhigonematoidea remain unsolved.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, no nematodes were observed on the body surfaces of alates, workers, larvae, eggs, and most of the inquilines. Even in the millipedes, which commonly harbor internal parasites 62–64 and external phoretic nematodes 65 , no nematodes were isolated. For inquilines, nematodes were only found beneath the elytron of coleopteran inquilines, which is a site that is not likely to be cleaned by allogrooming behavior in termites.…”
Section: Discussionmentioning
confidence: 99%